Impact of Baseline Glycemic Control on Residual Cardiovascular Risk in Patients With Diabetes Mellitus and High‐Risk Vascular Disease Treated With Statin Therapy. Issue 1 (7th January 2020) - Menon, Venu; Kumar, Anirudh; Patel, Divyang R.; St. John, Julie; Wolski, Kathy E.; McErlean, Ellen; Riesmeyer, Jeffrey S.; Weerakkody, Govinda; Ruotolo, Giacomo; Cremer, Paul C.; Nicholls, Stephen J.; Lincoff, A. Michael; et al.
Abstract : Background: The contemporary impact of glycemic control on patients with diabetes mellitus at high cardiovascular risk remains unclear. We evaluated the utility of hemoglobin A1c (HbA1c) as a marker of risk on the composite end point of cardiovascular death, nonfatal myocardial infarction, stroke, hospitalization for unstable angina, and coronary revascularization in an optimally treated population with diabetes mellitus and established coronary artery disease enrolled in the ACCELERATE (Assessment of Clinical Effects of Cholesteryl Ester Transfer Protein Inhibition With Evacetrapib in Patients at a High Risk for Vascular Outcomes) trial. Methods and Results: We included all patients with established diabetes mellitus and measured HbA1c (N=8145) and estimated Kaplan‐Meier (KM) events rates, stratified by increasing baseline HbA1c levels censored at 30 months. We then performed a multivariable regression for the primary end point. Increasing baseline HbA1c was strongly associated with the occurrence of the primary end point (KM estimate, 12.6–18.2; P <0.001). Increasing baseline HbA1c was also associated with the triple end point of death, nonfatal myocardial infarction, and stroke (KM estimate, 7.8–11.3; P =0.003) as well as the individual end points of nonfatal myocardial infarction (KM estimate, 3.1–7.0; P <0.001), hospitalization for unstable angina (KM estimate, 1.8–5.0; P =0.003), and revascularization (KM estimate, 7.3–11.1; P =0.001), although not stroke (KM estimate, 1.4–2.4; P =0.45). The rates of cardiovascular mortality (KM estimate, 2.6–4.3; P =0.21) and all‐cause mortality (KM estimate, 4.8–5.9; P =0.21) were similar regardless of baseline HbA1c levels. When adjusting for relevant baseline characteristics, baseline HbA1c was an independent predictor for the primary end point (hazard ratio, 1.06; 95% CI, 1.02–1.11; P =0.003). Conclusions: Glycemic control, as measured by HbA1c, remains strongly and independently associated with cardiovascular outcomes in high‐risk patients with diabetes mellitus on statin therapy. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01687998.